The Determinants of Retirement Planning within Couples in Ireland - Karina Doorley; Anne Nolan (Institute of Labor Economics (IZA), 2019)
Financial literacy is higher for men than for women and high financial literacy has been linked to higher wealth and better retirement planning. However, relatively little is known about the decision making process for retirement savings within couples and about how the gap or interaction between the financial literacy of members of a couple influences their preparation for retirement. This paper investigates the relationship between the financial literacy of members of pre-retirement couples and their level of wealth and financial stress using TILDA data for Ireland. We find that joint financial literacy is more highly correlated with household wealth, particularly real estate, than the financial literacy of individual members of the couple but that, where individual level financial literacy is associated with wealth, it is the financial literacy of the man in the couple which plays the most important role.
Keywords: J32; E21; D14; 330; retirement; financial literacy; wealth; couples